Learning a deep neural network for predicting phishing website - Das, Robat; Hossain, Md. Mukhter; Islam, Shariful; Siddiki, Abujarr (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.